Lateral decubitus position to facilitate pelvic examination of the patient with severe obesity - Daniel M. Breitkopf (BMC, 2021)
Abstract Background Patients with elevated BMI pose a number of challenges for the gynecologist. Pelvic examination may be more difficult due to adiposity in the perineum and labia, increasing the distance between the vulva and cervix. The objective of the current work was to describe use of the lateral decubitus position to improve visualization of the cervix in women with severe obesity. Methods A case series was collected. From 7/1/2010 until 1/31/2020, all records of patients with obesity and unsuccessful cervical visualization during pelvic exam in the dorsal lithotomy position in the author's clinical practice were reviewed after obtaining Mayo Clinic Institutional Review Board approval. For the lateral decubitus position, the patient was asked to lie on her side on the exam table, facing away from the examiner with knees bent. An assistant elevated the upper bent leg 45 degrees from horizontal, exposing the perineum. A vaginal speculum was then placed in the vagina with the posterior blade toward the anus. The speculum was opened gently as would be done with examination in dorsal lithotomy position until the cervix was visualized. Results Eleven patients with severe obesity in the gynecologic practice of the author with prior unsuccessful cervical visualization in dorsal lithotomy position were examined in the lateral decubitus position. In all but one case the cervix was successfully visualized in the lateral decubitus position and all intended intrauterine procedures were successfully performed. Conclusions In this case series, the use of the lateral decubitus position appears to improve visualization of the cervix in the outpatient setting among women with severe obesity. Consideration should be given to use of the lateral decubitus position when the cervix cannot be visualized in the dorsal lithotomy position.